2009
DOI: 10.1093/rheumatology/kep413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dual endothelin receptor antagonist bosentan on Raynaud's phenomenon secondary to systemic sclerosis: a double-blind prospective, randomized, placebo-controlled pilot study

Abstract: European Union Drug Regulating Authorities Clinical Trials, https://eudract.emea.europa.eu, EudraCT-Nr 2004-002686-21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 17 publications
4
35
1
1
Order By: Relevance
“…At present, there is no evidence base to support the use of ET-1 receptor antagonists for the treatment of Raynaud's phenomenon in the absence of digital ulcers. A single-centre, double-blind, parallel-group trial of 17 patients with SSc (but without digital ulcers) reported no benefit in terms of Raynaud's symptoms from 16 weeks' treatment with bosentan [34].…”
Section: Endothelin-1 Receptor Antagonismmentioning
confidence: 99%
“…At present, there is no evidence base to support the use of ET-1 receptor antagonists for the treatment of Raynaud's phenomenon in the absence of digital ulcers. A single-centre, double-blind, parallel-group trial of 17 patients with SSc (but without digital ulcers) reported no benefit in terms of Raynaud's symptoms from 16 weeks' treatment with bosentan [34].…”
Section: Endothelin-1 Receptor Antagonismmentioning
confidence: 99%
“…Bosentan did not improve the frequency, duration, pain or severity of RP attacks. While Bosentan may prevent digital ischemic ulcers in patients with SSc is not effective in RP treatment [ 85 ]. …”
Section: Endothelin-1 Inhibitormentioning
confidence: 99%
“…Эффективность бозентана в отношении дигитальных ишемических нарушений была показана в двух плацебо-контролируемых рандомизированных испытаниях (RAPIDS-1 и RAPIDS-2), включающих 210 пациентов с ССД [42,43]. Бозентан в начальной дозе 62,2 мг дважды в день в течение 4 нед, а затем 125 мг дважды в день в тече-ние 12 нед статистически значимо снижал частоту возник-новения новых дигитальных язв (на 48%) в сравнении с плацебо.…”
Section: системная красная волчанкаunclassified